Sensory Properties of Dadih Jelly Candy with The Addition of Clitoria Ternatea Flower Extract - Indri Juliyarsi; Sri Melia; Rizki Dwi Setiawan; Sugeng Pangestu (Universitas Teuku Umar, 2023)
An essential aspect of food product development is the sensory evaluation of product characteristics to test consumer acceptance. Characteristic properties, such as color, texture, flavor, and aroma, significantly affect the perception and acceptance of consumers. This study aimed to determine the effect of adding various concentrations of Clitoria ternatea flower (CTF) extract to dadih jelly candy on the physical properties of color and sensory properties, especially on quality characteristics and levels of consumer acceptance, using a hedonic test. This study used an experimental randomized block design divided into five treatments with the addition of CTF extract at concentrations of 0%, 0.5%, 1%, 1.5%, and 2%. The results showed that the CTF extract had a significant effect on the level of brightness (L*), the hedonic quality of color, and the hedonic color test, but had no significant effect on the value of a* (redness), b* (yellowness), and the hedonic quality and hedonic test of texture, flavor, and aroma of dadih jelly candy. The addition of 0.5% CTF extract was characteristic of dadih jelly candy that the panelists liked the most. It has a slightly soft texture, slightly sweet flavor, slightly dadih aroma, and high brightness.